IMPROVEMENT OF DRASTIC METHODS RATING CRITERIA IN GROUNDWATER POLLUTION ANALYSIS IN CITY BANDUNG - MULYANA SUPRIATNA (NIM: 25314749 ), ADI
Protection of groundwater resources can be made by creating a vulnerability map of groundwater pollution. The information obtained regarding the potential distribution of groundwater pollution vulnerability in a region can be used as a reference in sustainable development. DRASTIC method is one of the instruments to evaluate the susceptibility of groundwater pollution. This method is quite popular and widely used by researchers because it is well used on a regional scale. However, seven parameters (groundwater depth, precipitation, aquifer media, soil media, topography, vadose zone, hydraulic conductivity) were used as the basis for the analysis did not add land cover parameters as aspects of human activities that could potentially increase vulnerability. Based on the above, the development of assessment criteria method is to include the land cover parameters. In addition, adjustments on the parameters and weights associated with the condition of the study area in the city of Bandung. Development of assessment criteria conducted using Hierarchical Process Analysis (AHP) method with questionnaires distributed to stakeholders (academics, government and society) amounted to 30 samples. After obtaining the weights for land use parameters, the next step is to map the vulnerability of groundwater pollution with the help of Geographic Information System (GIS) using overlay analysis on the maps that have been made based on DRASTIC method development parameters. The research location is located in Bandung, West Java Province, Indonesia. The result of the analysis shows that the addition field parameter used in groundwater pollution analysis in Bandung City can increase the sensitivity of the assessment. In addition, the sensitivity of development methods is better than the DRASTIC method because of the wider spread of high vulnerability zones.